2007
DOI: 10.4081/ijas.2007.s2.948
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica: New buffalo (Bubalus bubalis) parasitosis in the province of Corrientes, Argentina

Abstract: The goal of this paper is to study the recent appearance of Fasciola hepatica parasitizing different buffalo (Bubalus bubalis) populations in the province of Corrientes. These animals share pastures with Bos taurus, Bos indicus and their crossbreds. Samples show a 28.5% positivity and a tendency to expand to other cattle. Until the year 2000, buffaloes were considered free of this disease. The paper also describes the importance of distomatosis and the potential economical losses due to a reduced productivit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Kobak and Pilarczyk (2012) found F. hepatica in 32% of buffaloes in the Notecka Forest region in Poland, which is almost twice the rate of infection with the present study. Racioppi et al (2007) also found high prevalence of F. hepatica infection (28.5%) in the province of Corrientes, Argentina. Buffaloes are usually exposed to a higher risk of infection with snail-borne helminths due to their tendency to seek rivers, pools or swamps for wallowing (Cockrill, 1974).…”
Section: Discussionmentioning
confidence: 95%
“…Kobak and Pilarczyk (2012) found F. hepatica in 32% of buffaloes in the Notecka Forest region in Poland, which is almost twice the rate of infection with the present study. Racioppi et al (2007) also found high prevalence of F. hepatica infection (28.5%) in the province of Corrientes, Argentina. Buffaloes are usually exposed to a higher risk of infection with snail-borne helminths due to their tendency to seek rivers, pools or swamps for wallowing (Cockrill, 1974).…”
Section: Discussionmentioning
confidence: 95%
“…Hasta el año 2000 los muestreos coprológicos negativos indicaban que los búfalos se encontraban libres de esta enfermedad en nuestra zona de influencia. Ese año se reportaron los primeros casos de decomisos de hígados infestados por F. hepatica en animales adultos faenados para consumo de carne 12 . La fasciolosis en bubalinos apareció cuando éstos se introdujeron en lugares previamente habitados por bovinos infestados, situación que demuestra que el parásito se transmite a los búfalos que comparten su hábitat con bovinos 7 .…”
Section: Resultados Y Discusiónunclassified
“…In India, goats were more infected than buffaloes [308]. Also, overall caprine fasciolosis was observed to be 20.75% in Bangladesh [309]. Recently, in Corrientes, Argentina, appearance of fasciolosis was observed in different buffalo populations showing 28.5% prevalence rate [310].…”
Section: Economic and Public Health Impactmentioning
confidence: 99%